2019
DOI: 10.37358/rc.19.9.7509
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Nanoparticles for Acidic Mine Waters Remediation

Abstract: Mining activities have a high negative impact on the environment and on human health. Environmental impacts can result in contamination of surface water, groundwater, soil and air. Large volumes of wastewater produced by mining activities have to be remediated before being discharged into the environment. Due to the complex composition of wastewater coming from the mining industry and because their negative impacts, numerous remediation techniques have been applied. Adsorption is one of the most extensively u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The vibrations registered at 1638 cm -1 , 1633 cm -1 and 1606 cm -1 are assigned to NH 2 -bending (amino groups) specific to chitosan structure from the three samples [13,14]. It can be observed that the specific peaks of chitosan are found at the specified wavenumbers for all the three analyzed samples, which confirms its structure.…”
Section: Resultssupporting
confidence: 55%
“…The vibrations registered at 1638 cm -1 , 1633 cm -1 and 1606 cm -1 are assigned to NH 2 -bending (amino groups) specific to chitosan structure from the three samples [13,14]. It can be observed that the specific peaks of chitosan are found at the specified wavenumbers for all the three analyzed samples, which confirms its structure.…”
Section: Resultssupporting
confidence: 55%
“…Numerous studies have been carried out on the remediation of Pb(II) and Cd(II) ions in industrial effluents and aqueous solutions by adsorption. The following adsorbent materials have been used: activated carbon and its derivatives [6], clays [7], natural and synthetic zeolites [8,9], hydroxyapatite and its composites [10], hydroxides [11], carbon nanotubes [12], simple and small oxides [13,14], silicates and their derivatives [15,16], magnetic nanoparticles [17][18][19], lignin and its derivatives [20], chitosan-based materials [21], geopolymers [22], metal-organic compounds [23], food waste [24], agricultural waste [25], industrial waste [26]. Among these, porous materials are considered alternative adsorbents with improved adsorption performance compared to activated carbon and other conventional adsorbent materials.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of wastewater containing Pb 2+ is inevitably produced from non-ferrous metal mining and smelting [1][2][3], lead-acid batteries [4,5] and other chemical production processes [6]. Because of its non-degradability and the enrichment in natural circulation systems Pb 2+ may cause serious harm to humans, animals and plants [7,8].…”
Section: Introductionmentioning
confidence: 99%